2019
DOI: 10.21920/recei72019515537544
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da alfabetização científica de alunos do ensino médio de um colégio de São Paulo

Abstract: A alfabetização científica está relacionada com o entendimento público dos conhecimentos científicos e tecnológicos que são capazes de capacitar a população para atuar como cidadãos. O presente estudo, teve por objetivo avaliar a alfabetização científica dos alunos concluintes da terceira série do ensino médio de um colégio particular de São Paulo. Participaram da pesquisa 123 alunos, os quais responderam ao Teste de Alfabetização Científica Básica (TACB). A análise revelou que apenas 55 alunos foram considera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Comparing the results with studies that evaluated the scientific literacy level of students in this cycle of education, it is observed that the amount of scientifically literate students found in this research is higher than those cases. The results of Coppi and Sousa (2019b), Rachmatullah, Diana and Rustaman (2016), Koedsri and Ngudgratoke (2018), Jufri, Hakim and Ramdani (2019), Vizzotto et al (2020) and Utami and Hariastuti (2019) evidenced that most of the students assessed were not considered scientifically literate. It is worth noting that this comparison should be made with caution, since the instruments used, the number of participants and the contexts of application were not the same.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Comparing the results with studies that evaluated the scientific literacy level of students in this cycle of education, it is observed that the amount of scientifically literate students found in this research is higher than those cases. The results of Coppi and Sousa (2019b), Rachmatullah, Diana and Rustaman (2016), Koedsri and Ngudgratoke (2018), Jufri, Hakim and Ramdani (2019), Vizzotto et al (2020) and Utami and Hariastuti (2019) evidenced that most of the students assessed were not considered scientifically literate. It is worth noting that this comparison should be made with caution, since the instruments used, the number of participants and the contexts of application were not the same.…”
Section: Resultsmentioning
confidence: 93%
“…When compared to the studies that performed this type of analysis, even though used the Test of Basic Scientific Literacy, a difference in the students' scores in the subtests is perceived. In all these studies (CAMARGO et al, 2011;SOUSA, 2019bSOUSA, , 2019aGARCIA, 2015;NASCIMENTO-SCHULZE;WACHELKE, 2006;ÖZDEM et al, 2010;RIVAS;MOÇO;JUNQUEIRA, 2017;VIZZOTTO;DEL PINO, 2020a, 2020bVIZZOTTO;MACKEDANZ, 2018), it was found that the subtest in which students obtained the best performance was in that of the CS and the worst was among the subtests of the NS and ISTS.…”
Section: Resultsmentioning
confidence: 99%
“…Of those that applied the TBSL and its versions, all revealed that the best results were identified in the subtest of the science content knowledge. At the same time, the worst were evidenced in the subtest of the nature of science by Sousa (2019b), Nascimento-Schulze et al (2006), Özdem et al (2010), Rivas et al (2017), Vizzotto and Mackedanz (2018) and on the subtest of the impact of science and technology on society by Coppi and Sousa (2019a), Lima and Garcia (2015), Vizzotto (2019) and Vizzotto and Del Pino (2020a). Camargo et al (2011) found that first-year students and teachers scored worse on the nature of science subtest, while for final-year students this occurred on both subtests.…”
Section: Study Results: Performance On the Dimensions Of Scientific L...mentioning
confidence: 99%
“…Considerando-se o resultado geral, 57% dos estudantes alcançaram o nível de alfabetizados cientificamente. Esse resultado indica que os respondentes atingiram um percentual de alfabetização científica satisfatório quando comparado com os desempenhos de uma escola particular de São Paulo (44,7%) [16] e com as redes pública (29,3%) e particular (69,1%) de Santa Catarina e Criciúma [17] .…”
Section: Avaliação Do Nível De Alfabetização Científica De Estudantes...unclassified
“…A Tabela 1 representa o desempenho dos participantes em função dos Eixos de Miller [14] . Tal comportamento também foi observado na literatura [16] , reforçando a necessidade de implementar ações educativas direcionadas ao eixo 2.…”
Section: Avaliação Do Nível De Alfabetização Científica De Estudantes...unclassified